THE INFLUENCE OF ISLAMIC RELIGIOSITY, ONLINE CUSTOMER REVIEWS, AND EASE OF SHOPPING ON CONSUMER PURCHASE DECISIONS THROUGH THE SHOPEE MARKETPLACE - Rofiqo, Azidni; Latif, Abdul; Khoiruddin, Irfan (EKOBIS SYARIAH, 2024)
This quantitative research discusses e-commerce in relation to online customer reviews and ease of shopping and its influence on purchasing decisions through Shopee e-commerce. This study aims to analyze the influence of Islamic religiosity, online customer reviews, and ease of shopping on customer purchase decisions on the Shopee Marketplace. The analysis method used was multiple linear regression using IBM SPSS 23 software. Primary data is obtained through the distribution of questionnaires to respondents who are active users of Shopee. The research sample consisted of the number of respondents determined by the slovin method, taken from shopee online customer data La Tansa Bookstore and Stationery. The results of the study according to the partial test (t), the Islamic Religiosity variable did not affect the purchase decision through shopee e-commerce La Tansa Bookstore and Stationery on the results of the multiple regression test. Conversely, both Online Customer Reviews and Ease of Shopping have a positive impact on purchasing decisions through shopee e-commerce La Tansa Bookstore and Stationery. The test results showed that 73.7% was accounted for by the dependent variables, indicating a significant influence on the Independent variables